Evaluation of Patients with Palpitation - Almissari , Ahmed M Athab (Diyala Journal of Medicine, 2019)
Background: palpitation is an awareness of the heart beat. The pattern of palpitations especially when correlated to the pulse may help narrow the differential Diagnosis: rapid, regular palpitations are noted with supraventricular tachycardia or ventricular tachycardia; rapid, irregular palpitations are noted with a trial fibrillation; and “skipped beats” are noted with premature atria or ventricular contractions. Objective : the aim of this study to determine the causes of palpitation in 200 patients seeking medical advice in baquba teaching hospital –out patient consultation clinic. Patient and Methods: 200patients presented with palpitation at baquba teaching hospital – out patient consultation clinic were considered for this study 85 male(42.5) and 115female(57.5), full history taking, physical examination with simple available investigation and psychiatric screening done for them. Results: A cause of palpitation was determined in 85% of patients. The causes was cardiac in 40%, psychiatric causes in30%, miscellaneous in 15% and unknown causes in 15%.